This is not homework. I do it for fun and learning.
I use the Logic Book.
Problem has to be done in SD+.
How to prove the following argument :
|- [~A =>(~B=>C)]=>[(A v B) v (~~B v C )]
I started by assuming the antecedent and using ND to the best of my ability to get the conclusion. But I only land up getting A vB or (~~B v C) which is ~B=>C (impl) but not both
Maybe in order to get B deriving a contradiction would help, since if I assume ~A =>~B
In effect, I was able to derive one of the consequents,but not the other
I tried working backwards and still got stuck
I request help or hints on how to resolve this dilemma